Private equity and Covid-19 - Gompers, Paul A.; Kaplan, Steven N.; Mukharlyamov, Vladimir (Journal of Financial Intermediation, 2022)
We survey more than 200 private equity (PE) managers from firms with $1.9 trillion of assets under management (AUM) about their portfolio performance, decision-making and activities during the Covid-19 pandemic. Given that PE managers have significant incentives to maximize value, their actions during the pandemic should indicate what they perceive as being important for both the preservation and creation of value. PE managers believe that 40% of their portfolio companies are moderately negatively affected and 10% are very negatively affected by the pandemic. The private equity managers—both investment and operating partners—are actively engaged in the operations, governance, and financing in all of their current portfolio companies. These activities are more intensively pursued in those companies that have been more severely affected by the Covid-19 pandemic. As a result of the pandemic, they expect the performance of their existing funds to decline. They are more pessimistic about that decline than the venture capitalists (VCs) surveyed in Gompers et al. (2021). Despite the pandemic, private equity managers are seeking new investments. Rather than focusing on cost cutting, PE investors place a much greater weight on revenue growth for value creation. Relative to the 2012 survey results reported in Gompers, Kaplan, and Mukharlyamov (2016), they appear to give a larger equity stake to management teams and target somewhat lower returns.